Review of the Fund's Involvement in the G-20 Mutual Assessment Process. (Policy Papers; Policy Paper, 2011)
This paper responds to the Board's call for a review of the Fund's role in the G-20 Mutual Assessment Process (MAP) after about a year of implementation. The review covers the period from December 2009 to the April 2011 meeting of the G-20 Finance Ministers and Central Bank Governors in Washington. It considers the Fund's inputs against the background of the evolving MAP and discusses expectations for this work going forward. The paper does not review the G-20 MAP itself. The implications of broader G-20 Fund cooperation for the Fund's own surveillance will be discussed in the forthcoming TSR.